ICT integration at the University of Antioquia: a puzzle to put together - Forero Arango, Ximena; Segura Jiménez, Herlaynne (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
This article seeks to recover and systematize the history of the main initiatives for integrating technology into education that have emerged at the University of Antioquia. Despite the fact that the subject is of great importance for educational innovation and the improvement of the training processes of the second largest public university in Colombia, the work of these initiatives has not been known or recognized within the institution for more than thirty years. The investigations show that although several projects have been carried out independently, they share processes and objectives that allow sharing learning and collaboratively building a “unity in diversity”. Systematizing the history of these five initiatives was the opportunity to find out from primary sources –personal and documentary– what were the circumstances and events that marked the path of each one of these projects, which in some cases arose from the investigation, in others from the extension and in others as a need for teacher qualification and expansion of coverage.